Time and the self: A re-examination of Hume's account of personal identity. - Miller, Jonathan Charles. (University of Ottawa (Canada), 2002)
According to Hume, all true ideas must have distinct preceding impressions. Since there is no distinct impression of the self, Hume states the self is merely a succession of perceptions. Similarly, Hume states that time, as the idea of succession, does not derive from a distinct impression, but is simply the "manner" (succession) in which perceptions appear. However, since Hume says that we perceive the manner, we must perceive some type of impression for succession, which means that Hume paradoxically asserts that we can distinguish succession as the manner, yet this ability to distinguish the manner from the perceptions does not mean succession itself is a distinct impression. Hume's problem then is to show convincingly how it is possible to somehow isolate succession from the perceptions in succession so as to notice the manner, yet still be able to answer what then is succeeding. Although Hume fails to solve this Succession Puzzle, a solution can be found within his philosophical principles. This thesis tries to show that Hume does not recognize the different structures between time and space, and confuses time as both succession and duration. (Abstract shortened by UMI.)
Keywords: Philosophy.